The risk of automation in Latin America - Irene Brambilla; Andrés César; Guillermo Falcone; Leonardo Gasparini; Carlo Lombardo (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
In this paper we characterize workers' vulnerability to automation in the near future in the six largest Latin American economies as a function of the exposure to routinization of the tasks that they perform and the potential automation of their occupation. We combine (i) indicators of potential automatability by occupation and (ii) worker's information on occupation and other labor variables. We find that the ongoing process of automation is likely to significantly affect the structure of employment. In particular, unskilled and semi-skilled workers are likely to bear a disproportionate share of the adjustment costs. Automation will probably be a more dangerous threat for equality than for overall employment.
Keywords: J21; J23; J24; O33; 330; jobs; employment; income distribution; automation; routinization; Latin America